Probability of price crashes, rational speculative bubbles, and the cross-section of stock returns - Jang, Jeewon; Kang, Jangkoo (Journal of Financial Economics, 2019)
We estimate an ex ante probability of extreme negative returns (crashes) of individual stocks as a measure of potential overpricing and find that stocks with a high probability of crashes earn abnormally low returns. Stocks with high crash probability are overpriced regardless of the level of institutional ownership or variations in investor sentiment, and moreover, they exhibit increasing institutional demand until their prices reach the peak of overvaluation. We also find that institutional investors who overweight high crash probability stocks outperform the others, indicating that they have skill in timing bubbles and crashes of individual stocks. Our findings imply that sophisticated investors may not always trade against mispricing but time the correction of overpricing, and suggest that the crash effect we find could arise at least partially from rational speculative bubbles, not entirely from sentiment-driven overpricing.